Use of the Gower algorithm in determining genetic divergence among genotypes of Carthamus tinctorius L. (Research, Society and Development, 2022)
Safflower is a crop with a high capacity to develop and produce satisfactorily under adverse environmental conditions. Thus, the analysis of genetic diversity in gene banks is an important component in the selection of genotypes with desirable characteristics that promote genetic gain in the offspring. Given the above, the present work aimed to estimate the genetic divergence between safflower genotypes using the Gower algorithm for the joint study of quantitative and qualitative data. The experiment was developed in the experimental area of the Mato Grosso Company for Research, Assistance and Rural Extension, in the city of Cáceres-MT. We evaluated 124 genotypes of Carthamus tinctorius L. through their agronomic and morphological characteristics. The divergence among the genotypes was estimated by multivariate analysis, based on Gower's algorithm for the 21 characteristics.  Variability among individuals was detected, demonstrating the effective Gower method to estimate the divergence between genotypes.